Anne Tyler : a critical companion - Bail, Paul (Critical companions to popular contemporary writers., 1998)
In this study Paul Bail shows us how Tyler constructs the complex reality of life through character, narrative point of view, theme, and literary devices. With the exception of Tyler's earliest two novels, which she prefers to forget, a chapter is devoted to each of the other novels she has written. Following a biographical chapter that relates Tyler's life to her work, Bail discusses the novels within the literary tradition of Southern regional literature, women's literature, and popular culture. He also explores the influence of religion on her writing. Bail also offers an alternate critical approach from which to read the novel, such as feminist or multicultural criticism. This study is ideal for students and readers of Anne Tyler and will enrich the reading and appreciation of her novels.